Influence of Leadership Competence, Achievement Motivation, and Organizational Learning Culture on Administrative Staff Performance at Universitas Gadjah Mada Graduate School - Nugroho, Tri (MyResearch ID Publishing, 2024)
Purpose – This study aims to examine the factors influencing the performance of administrative staff at the Graduate School of Universitas Gadjah Mada (UGM). Specifically, the research focuses on the roles of leadership competence, achievement motivation, and organizational learning culture in determining staff performance, addressing gaps in previous studies that lacked a comprehensive integration of these factors. Methods/Design/Approach – A quantitative approach with an explanatory survey design was employed. Data were collected using questionnaires distributed to all 89 administrative staff at the UGM Graduate School, yielding 78 valid responses. The relationships between leadership competence, achievement motivation, organizational learning culture, and performance were analyzed using multiple linear regression. Validity and reliability tests, alongside classical assumption tests, were conducted to ensure the robustness of the model. Findings – The results demonstrate that both leadership competence and achievement motivation positively and significantly affect staff performance. Achievement motivation was identified as the most dominant factor, while organizational learning culture showed no significant influence. The model explains 57.2% of the variance in staff performance, indicating that other unexplored factors may contribute to performance outcomes. Originality/Value – This study provides a novel integration of leadership competence, achievement motivation, and organizational learning culture within a single analytical model, contributing to the literature on human resource management in higher education in Indonesia. The findings offer a comprehensive understanding of key factors influencing staff performance in public higher education institutions. Practical Implications – The findings suggest that higher education management should prioritize leadership development and motivation enhancement initiatives to improve staff performance. Although the organizational learning culture did not significantly affect performance, efforts should still be made to foster a learning environment to support long-term organizational success. Keywords Leadership competence, achievement motivation, organizational learning culture, staff performance, higher education management Paper type Research paper